Aplikasi Apotek dengan Bahasa Pemrograman PHP: Studi Kasus Pada K-24 Karawitan Kota Bandung - Aisyah; Tarsinah Sumarni (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Information system nowadays is very important in pharmacy operation management. In running the pharmacy, K-24 karawitan bandung Bandung city is required to be able to provide the best service to customers by ensuring the necessary drugs are available and managing drug inventory properly. However, in managing the drugs, there are still many pharmacies that experience obstacles in terms of managing drug supplies and needs, especially in drug supply, inventory control and business management. In addition, with the development of information technology, many consumers buy medicines online through the local web. However, creating a local pharmacy web is not an easy thing. Therefore, research on how to create a local medical web using SQL is still very important and important to do. This research can provide new insights into how best to use SQL in building a pharmacy website, and how hospital websites can help make it easier for customers to buy medicine. This research can also provide benefits for K-24 karawitan bandung city Bandung pharmacies who want to use SQL technology in their business and improve efficiency in inventory management and business pharmacy management.